Ações civis públicas e seu papel na promoção de uma educação de qualidade - Torres, Arthur José Pavan (2019)
The law aims at the restoration of social peace, that is, its purpose is to stabilize expectations. Contemporary society is complex and demands other legal mechanisms that can contribute positively to the egalitarian enjoyment of social rights. Judicializing the right to education, through public civil actions, can contribute to the improvement of the quality of basic education in Brazil. It is possible to reduce the proposition of individual judicial demands in educational matters, with the concentration of certain demands in a few actions, avoiding individual decisions fragmentary, that can generate numerous impacts in the contribution of financial resources of the public budget, in the attendance of individual decisions. The extension of the Judiciary's activity, in the analysis of collective actions related to the delivery of social rights, generates the discussion about the phenomena of judicial activism and the judicialization of public policies. From this perspective, it is observed that the process must reach the greatest extent possible, identifying its multiple purposes, from the analysis of its immediate and mediate effects. Therefore, the process must be geared to meeting broader social goals, related to the rights demanded and others that, in most cases, can transcend them, to the point of serving as arenas of democratic debate.